The Effect of Variety Seeking and Price Perception on Brand Switching Among Consumers on Hijab Products (Elzatta Case Study) - Sari, Nihayah Yustika; Misbak , Misbak; Maulany, Soesanty (Journal Research of Social Science, Economics, and Management, 2026)
The Indonesian hijab industry has experienced significant growth due to the increasing number of Muslim women wearing hijabs and the rapid development of modest fashion trends. This dynamic market environment has intensified competition among hijab brands, prompting consumers to frequently switch brands based on changing preferences and evaluations. This study examines the effects of variety seeking and price perception on brand switching behavior among consumers of Elzatta hijab products in Cirebon City. A quantitative associative research design was employed using a survey method. Data were collected from 218 female respondents who had purchased Elzatta hijabs as well as competing hijab brands. The analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test the proposed hypotheses. The findings indicate that variety seeking has a positive and significant effect on brand switching, suggesting that consumers with a stronger desire for novelty and product variation are more likely to switch brands. In addition, price perception also has a positive and significant influence on brand switching and emerges as the dominant factor affecting consumer decisions. Consumers are more inclined to switch brands when they perceive that product prices do not align with the quality and value received. The model explains 48.1% of the variance in brand switching behavior. In conclusion, both psychological factors, represented by variety seeking, and economic considerations, reflected in price perception, significantly influence brand switching among Elzatta hijab consumers, with price perception playing a more substantial role in shaping switching behavior.